ChemInform Abstract: Synthesis and Biological Evaluation of Some 2‐(3, 5‐Dimethyl‐1H‐pyrazol‐1‐yl)‐1‐arylethanones: Antibacterial, DNA Photocleavage, and Anticancer Activities. Issue 48 (2nd December 2014) - Kumar, Vinod; Kaur, Kamalneet; Karelia, Deepkamal N.; Beniwal, Vikas; Gupta, Girish Kumar; Sharma, Arun K.; Gupta, Akhilesh Kumar
Abstract A novel, mild, green, fast, and highly regioselective one‐pot protocol to prepare title compounds (III) is developed.